Perspective of Adults With Neurofibromatosis 1 and Cutaneous Neurofibromas: Implications for Clinical Trials. Issue 7 (17th August 2021) - Cannon, Ashley; Pichard, Dominique C.; Wolters, Pamela L.; Adsit, Sarah; Erickson, Gregg; Lessing, Andrés J.; Li, Peng; Narmore, Whitney; Röhl, Claas; Rosser, Tena; Widemann, Brigitte C.; Blakeley, Jaishri O.; et al.
Abstract : Objective: To assess the perspectives of adults with neurofibromatosis 1 (NF1) regarding cutaneous neurofibroma (cNF) morbidity, treatment options, and acceptable risk–benefit ratio to facilitate the design of patient-centered clinical trials. Methods: An online survey developed by multidisciplinary experts and patient representatives of the Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) cNF Working Group was distributed to adults with NF1 (n = 3, 734) in the largest international database of individuals with any form of NF. Eligibility criteria included self-reported NF1 diagnosis, age ≥18 years, ≥1 cNF, and ability to read English. Results: A total of 548 adults with NF1 responded to the survey. Respondents ranked appearance, number, and then location as the most bothersome features of raised cNF. Seventy-five percent of respondents considered a partial decrease of 33%–66% in the number or size of cNF as a meaningful response to experimental treatments. Most respondents (48%–58%) were willing to try available cNF treatments but were not aware of options outside of surgical removal. Regarding experimental agents, respondents favored topical, then oral medications. Most individuals (>65%) reported being "very much" or "extremely willing" to try experimental treatments, especially those with the highest cNF burden. Many respondents were not willing to tolerate side effects like nausea/vomiting (51%) and rash (46%). The greatest barriers to participation in cNF clinical trials were cost of participation and need to take time off work. Conclusions: Most adults with NF1 are willing to consider experimental therapies for treatment of cNF. These data will guide the design of patient-centered clinical trials for adults with cNF.